Improved Glow Discharge Polymer Removal from Beryllium Capsules Using Ozone. (3rd April 2021) - Bae, John; Xu, Hongwei; Kong, Casey; Baxamusa, Salmaan; Rice, Neal; Youngblood, Kelly; Alford, Craig; Stadermann, Michael
Abstract: Copper-doped beryllium spheres are an attractive ablator for inertial confinement fusion experiments. Beryllium spheres are made by sputtering beryllium onto spherical plastic mandrels which must then be removed through a hole that is laser drilled through the shell wall. The currently used mandrel material is glow discharge polymer. This material cannot be removed by solvent and must be "burned" out. The burnout process was originally performed by etching with dry air at 425°C, but this process can substantially roughen the inner surface, which can seed instabilities and increase mix during implosion experiments. In this paper, we explore the use of pure oxygen and ozone to reduce process temperature and improve inner and outer surface quality.